DUKUNGAN KELUARGA DENGAN PEMBERIAN ASI EKSKLUSIF PADA IBU MENYUSUI (Family Support and Exclusive Breastfeeding in nursing mother ) - Andriani, Dewi (JURNAL NERS LENTERA, 2017)
Introduction: Mother's Milk (ASI) is the best food for babies. Breastfeeding plays an important role in maintaining health and maintain the viability of the baby. During breastfeeding, in order to achieve exclusive breastfeeding , the mother needs support, one of which is the family support. Family support is very important for the smooth process of lactation and breastfeeding. The purpose of this study was to determine the relationship between family support and exclusive breastfeeding in nursing mothers in RW 01, Kelurahan Sidotopo Kecamatan Semampir Surabaya. Methods: This study design is the correlation design. The independent variable is the support of family and the dependent variable is exclusive breastfeeding. Samples taken by 30 respondents. Respondents were selected using the